Assessment of Cases of Suicide in Turkey Based on Turkish Statistical Institute Data - Gümüş, Burak; Özer, Erdal; Yıldırım, Ali; Çetin, İlhan (The Bulletin of Legal Medicine, 2010)
Suicides are evaluated as an important public, and psychologic problem globally without any socio-economical discrimination. In many countries they are the leading cause of mortality after traffic accidents .This study intends to evaluate the trend in cases of suicide occurred in Turkey with respect to age, gender, level of education, reasons for suicide attempts, and variations in its incidence within years, and compare them with global suicidal trend in the world. In our study suicide statstics of Turkish Statistical Institute (TUIK) related to years 2002-2009 were evaluated.. The data obtained were analysed using Windows SPSS 15.0 statistical package. The cases consisted of males (64.4%), and females (35.6%). Among all age groups a continual increase in the number of males committing suicide between 2002-2009 strikes our attention. Female suicide cases in age groups of 0-19, and 20-39 years demonstrated a decrease between 2002 and 2009, however an apparent increase is seen for females aged 40-59 or more than 59.. Educational levels of sucide committers were as follows: primary, and secondary school (62.9%), lycée (16.3%), and high school, college, and university (5.1%).. These cases were observedly categorized based on suicide agents as: hanging (47%), firearms (23.5%), chemical substances (14.2%), and fall from a height (9%). Unknown reasons (34.3%), diseases (23.8%), marital conflicts (15.1%), financial difficulties (10.2%), and sensual problems (6.7%) were blamed as reasons for suicide attempts for those cases committing suicide between 2002-2009 . According to WHO data, global mortality because of suicide attempts was % 1.6 In the year 2009 when total population of Turkey was 72.561.312 people, annual incidence of suicides was 0.4% According to United States (US) statistics for the year 2005, firearms (52.1%), hanging-drowning (22.1%), and self-poisoning (17.6%) were reported as suicide agents. When compared with the correspending incidences in the US, cases of suicide in Turkey have been observed 2.1-fold more frequently, while firearms are preferred more often (2.2 times higher) as suicide agents in the US. Key words: suicide, suicide methods, suicide, causes of suicide, forensic medicine